Larvicidal and Antifeedant Activity of Some Plants Extracts Against the Larvae of Helicoverpa Armigera (Hubner) - Ravi, G.; Dr.G.Sundararajan, (International Journal of Scientific Research and Management (IJSRM), 2020)
In the present study, selected some plants,  namely,  Andrographis paniculata Ness., Cardiospermum halicacabum L., Cassia tora L., Catharanthus roseus L (G) Don., Datura metal L., Eupatorium riparium and Mikania  micarantha were   screened  for  their  larvicidal   and  antifeedant  activity against  the larvae of  Helicoverpa  armigera (Hubner)  under  laboratory  conditions.  The  crude  extracts  of  all  the  selected plants  demonstrated  a  dose  dependent  increase  in  bioactivity.  However  the bioactivity  of  four  plants  namely,  A.paniculata,  Cassia tora L., C.halicacabum L., and Datura metal L. was significantly higher (p ≤ 0.05) than the  control  and  extracts  of  C.roseus,  E. riparium  and  M.micarantha. Methanol  extract  of  A.paniculata  caused  highest  oral  toxicity  with  larval mortality ranging between 29.00% and 58.22% across the test concentration (0.2%, 0.4% and 1% w/v) while extract of C.tora L., demonstrated the highest feeding deterrence with reduction in larval feeding by 59.92% and 76.61%  at  0.2%  and  0.4%  respectively.  Crude  extract  of  C.halicacabum L.,  leaves demonstrated  high  oral  toxicity  and  feeding  deterrence  while extract  of D.metel showed moderate level of oral toxicity as well as feeding deterrence at the highest tested concentration. Thus  it  may  be  concluded  that  four  out  of  the  selected plants  possess insecticidal property and can be further investigated for the development of a potent natural botanical insecticide.